Factors associated with post-treatment smoking among a diverse sample of cancer survivors in the US - Safa Elkefi; Corina T. Lelutiu-Weinberger; Jean-Marie Bruzzese; Alicia K. Matthews (Discover Public Health)
Abstract Objective This study aims to explore the prevalence of post-treatment smoking among cancer survivors and examines the association between smoking behavior and various demographic, psychosocial, and health perception factors. Methods We utilized cross-sectional data from the Health Information National Trends Survey (HINTS). Socio-demographic, psychosocial (mental distress, social isolation, and meaning and purpose in life), and health perception variables were assessed as correlates of smoking status. Descriptive statistics and logistic regression analyses were employed for analysis. Results Most participants were over 65 years old, female, and identified as White. Nearly 10% of all cancer survivors reported being current smokers, and 34.99% reported being former smokers. Lower socioeconomic status (less than a high school education and income levels below $20,000) was associated with higher rates of post-treatment smoking. Elevated levels of mental distress (OR = 3.85 [1.71–8.63], p < .001) and social isolation (OR = 2.55 [1.23–5.28], p = .029) were significantly associated with smoking. At the same time, a greater sense of meaning and purpose in life was linked to a lower likelihood of smoking (OR = 0.27 [0.12–0.59], p = .002). Moreover, positive health perceptions and confidence in managing health were inversely and significantly related to smoking behavior (OR = 0.29 [0.14–0.6], p = .005). Conclusions Despite the known adverse health effects of smoking, some cancer survivors continue to smoke post-treatment. As such, providers should continue to assess smoking status and facilitate smoking cessation treatment among cancer survivors. Mental health and psychosocial factors were identified as key risk factors for persistent smoking and should be considered in future initiatives to reduce smoking among cancer survivors.